The innovator's solution : creating and sustaining successful growth - Christensen, Clayton M., 1952-2020; Raynor, Michael E., ....- (Boston (Mass.) : Harvard Business Review Press, 2013)
"A seminal work by bestselling author Clayton M. Christensen, now with a refreshed package. In the international bestseller The Innovator's Dilemma, Clayton Christensen exposed the Achilles' heel of many companies: by ignoring the disruptive technologies that evolve to displace them, they help initiate their own demise. In The Innovator's Solution, Christensen and Michael Raynor take the idea of disruption one step further--explaining how companies can and should become disruptors themselves. Now with a new look, The Innovator's Solution proves just how timely and relevant these ideas continue to be in today's hyper-accelerated business environment. Christensen (author of the award-winning Harvard Business Review article, "How Will You Measure Your Life?"), and Raynor give usable advice on the business decisions crucial to achieving truly disruptive growth and propose guidelines for developing your own disruptive growth engine. Citing in-depth research and theories tested in hundreds of companies across many industries, The Innovator's Solution is an important addition to any innovation library and an essential read for entrepreneurs and business builders. Published by Harvard Business Review Press. "--
Keywords: Business & economics -- Decision-making & problem solving; Business & economics -- Management; Business & economics -- Strategic planning; Creative ability in business; Customer services; Disruptive technologies; Industrial management; Success in business